The Genetic Programs Specifying Kolmer–Agduhr Interneurons - Yang, Lixin; Wang, Feifei; Strähle, Uwe (Frontiers in Neuroscience, 2020)
Kolmer-Agduhr cells (KA cells) are a subgroup of interneurons positioned adjacent to the neurocoele with cilia on the apical surface protruding into the central canal of spinal cord. Despite KA cells were distingushed almost a century ago, their development and functions are only beginning to be unfolded. Studies have revealed the characteristics of KA cells in greater detail and extended our understanding of where the KA cells are distributed, when the KA cells are differentiated, and how the KA cells are specified by the extrinsic signaling and the unique combination of transcription factors in mouse and zebrafish. Cell lineage-tracing experiments demonstrate that two subsets of KA cells, named KA’ and KA’’ are differentiated from motoneurons progenitors and floor plate precursors in zebrafish and mouse. The KA’ and KA’’ cells derived from different progenitors or precursors, both of them, however share a common set of transcription factors. Intriguingly, the combination of transcription factors which promote acquisition of KA’ cells characteristics differs that of the KA’’ cells. In addition, KA’ cells appear to be different in neuronal targets and responses to bending of spinal cord to KA’’. In this review, we summarize what we currently know about genetic programs defining KA identity. We then discuss how the two subgroups of KA cells originated from two progenitors are genetically specified.